Mulheres quilombolas: território, gênero e identidade na comunidade negra Senhor do Bonfim, Areia/PB (2005-2018) - Santos, Geilza da Silva (2018)
The present dissertation, inserted in the research line of Teaching History and Historical Knowledge, aims to analyze the "place" of women in the Black Community of Senhor do Bonfim, located in the rural area of the city of Areia/PB. Emphasizing their contribution to the construction of the group identity, we will use the oral history in order to understand the relation between the black women with their land; their struggles and resistances based on the approach of their participation in the community and the territory. Concerning to the theoretical and methodological contribution we will be guided by the reflections brought by Maurice Halbwachs (1990) so that we can comprehend how the individual memory is linked to a collective memory; as well as Ecléa Bosi (1994) to understand the importance of the memory of the old for the construction of the history of the group; Tomaz Tadeu da Silva (2012) and Stuart Hall (2001, 2003) will help us to understand how it is built from the differences and according to the lived context; closer to Anthropology, a dialogue is established with Fredrik Barth (1998) and his thinking about ethnic groups and the formation of cultural boundaries. The concept of belonging to Jacques D'adesky (2001) linked to the territory from Rogério Haesbaert (1999, 2006) will be extremely important for our analysis considering the importance of the place where women live and especially their contributions in the constitution of an identity. Besides that, we use the concept of gender presented by Scott (1990), in order to understand how the social relations within the group are constructed. In view of the issues raised about our theme, we will use interviews, audiovisual sources, demographic census and institutional documents, relating them in a dialogical way to guide the way of our research.